Integrated Skills Approach (ISA) in writing class: A case study of Business English Communication (BEC) students of Universitas Negeri Makassar - Andi Hajar (International Journal of Humanities and Innovation (IJHI), 2022)
The study aims to describe (1) the nature of the Integrated Skills Approach in writing class, (2) whether the Integrated Skills Approach (ISA) is effective in facilitating the students to write English compositions. The study was conducted in the Business English Communication (BEC) writing class of the English Department, Faculty of Languages and Literature, Universitas Negeri Makassar. The subject of this study was the BEC students, consisting of 20 students. This study was essentially quantitative research. The data were taken from the students’ writing compositions and analyzed using the pre-experimental method with one group pre-test and post-test design. This design involves one group, which was pre-tested (X1), then exposed to treatment (T), and post-tested (X2). The study shows some results as follows: 1) Integrated Skills Approach (ISA) could enthusiastically involve the students in learning activities. 2) Integrated skills sequence leads the students to share ideas about the topic of writing composition. 3) Integrated Skills Approach (ISA) effectively facilitates students' English composition writing.